One hundred years of EEG for brain and behaviour research - Mushtaq, Faisal; Welke, Dominik; Gallagher, Anne; Pavlov, Yuri G.; Kouara, Layla; Bosch-Bayard, Jorge; van den Bosch, Jasper J. F.; Arvaneh, Mahnaz; Bland, Amy R.; Chaumon, Maximilien; Borck, Cornelius; He, Xun; et al. (My University, 2024)
On the centenary of the first human EEG recording, more than 500 experts reflect on the impact that this discovery has had on our understanding of the brain and behaviour. We document their priorities and call for collective action focusing on validity, democratization and responsibility to realize the potential of EEG in science and society over the next 100 years.
Keywords: electroencephalogram (EEG); electroencephalography; behavioural research; brain/physiology